Daniel Albright. Putting Modernism Together. Literature, Music, and Painting, 1872–1927. Baltimore: The Johns Hopkins UP, 2015. - Thomas C Connolly (Studies in 20th & 21st Century Literature, 2017)
Review of Daniel Albright. Putting Modernism Together. Literature, Music, and Painting, 1872–1927. Baltimore: The Johns Hopkins UP, 2015.
Keywords: Daniel Albright; Putting Modernism Together; Literature Music and Painting 1872–1927